Ultrastructural changes in the microvessels and perivascular space in cerebral infarction in the experiment - Voloshanska, O. O.; Tertyshnyi, S. i. (Морфологія / Morphologia / Morfologìâ, 2021)
Background. Ischemic stroke is the second most common cause of death after coronary heart disease and the most common cause of disability worldwide. Much of the recent basic research on stroke is concerned with the mechanisms underlying the dysfunction and adaptation of the neurovascular block, which includes the blood-brain barrier structures, microglia, neurons, and the extracellular matrix of the basement membrane. Isolated studies of recent years have been devoted to the issues of morphology and in particular the ultrastructure of the brain in ischemic injury. Meanwhile, only morphological studies can reveal the peculiarities of the response of cellular structures to the influence of various adverse factors. Objective – to investigate ultrastructural changes in the vessels of the brain and perivascular space in experimental ischemic heart attack. Methods. Experimental cerebral infarction was reproduced on 15 white Wistar rats by injection of a suspension of barium sulfate in sterile saline in a ratio of 1: 3 in the amount of 0.1 -0.3 ml. Three animals formed a control group. The material was collected in terms of: up to 3, 9, 12 days and more than 12 days from the beginning of the experimental action, followed by standard processing of the material for electron microscopy. Results. In the early stages of ischemic brain damage perivascular edema, destructive changes of capillaries with destruction of basement membranes are registered. Some microvessels undergo irreversible changes with deformation of the vascular lumen, pyknosis and lysis of endothelial nuclei, destruction and vacuolation of cytoplasmic structures, microvacuolation and edema of mitochondria with partial destruction of cristae and enlightenment of the mitochondrial matrix. In the endothelium with signs of coagulation processes in the cytoplasm and nucleus, changes in cell contacts were observed. Structural changes of vessels are combined with changes of perivascular processes of astrocytes. On days 9 and 12, the structure of the endothelium, perivascular astrocytes, and intercellular contacts are restored. Hyperplasia of intracytoplasmic structures, increase in mitochondria and length of cytoplasmic network are noted. In the cells of the perivascular environment and in the cytoplasm of pericytes a significant number of phagolysosomes is detected, in the long term in the perifocal areas of irreversible ischemic changes around the vessels is reparative astrogliosis. Conclusion. Ultrastructural changes of the microcirculatory part in the perifocal areas of ischemic lesions within 3 days are characterized by perivascular edema and destructive changes in the endothelium of capillaries and pericytes, damage to basement membranes, changes in cell contacts. After 9-12 days in the endothelium, the processes of intracellular regeneration increase, the ultrastructure of intercellular contacts is restored. A significant number of phagolysosomes is registered in the cells of the perivascular environment and in the cytoplasm of pericytes, and reparative astrogliosis is detected in the perifocal areas of irreversible ischemic changes around the vessels.